Towards painless and productive research relationships: reflections on study design by a researcher with chronic pain for participants with chronic pain - Wilkinson, Catherine (Frontiers in Pain Research, 2025)
Building flexibility into the research design of a study allows for responsiveness to the embodied and fluctuating nature of participants’ chronic illnesses, which may be shaped, for instance, by flare-ups and periods of remission of acute pain. Whilst the methodology literature has, to some extent, considered how to accommodate the pain of research participants when designing a study, consideration of how methodological choices are responsive to the researcher's pain needs has not to date been foregrounded. From the perspective of a researcher with Ankylosing Spondylitis (AS), a form of inflammatory arthritis characterized by chronic pain, and Crohn's disease, a type of inflammatory bowel disease, characterized by stomach and joint pain, this paper provides insight into pain and researcher-participant relationships, from the perspective of a researcher in pain, designing a study to accommodate her own pain needs, as well as anticipating the needs of prospective participants in pain. This paper proposes the use of flexible, remote, and asynchronous research methods as ways to make studies inclusive for researchers living with pain, whilst fostering the most fruitful research relationships with participants who also live with pain, thereby moving towards a position of shared vulnerability. It also highlights the relative absence of the researcher's needs and possible vulnerability in ethics forms and considered by research ethics committees, in comparison to the needs and vulnerability of participants.